Innovation Process in Public Service: Studying Innovation Process in Yogyakarta City Licensing Service Clinic Unit (KLIPPER) - M. RIZKI PRATAMA (Universitas Muhammadiyah Yogyakarta, 2018)
To date on Indonesia’s government performance, innovation agenda has encouraged public’s hope as bureaucracy reformation has been closer to policy failure. Innovation becomes a trend to make public’s ends meet, mainly innovation which is introduced by local governments. As the most innovative local governments, Yogyakarta City, has proceeded many thrive innovations from their local agencies such as Yogyakarta City Licensing Service Office. For long time, the office is recognized as good practice of public service provision in Indonesia. At that case, it can be assured through Licensing Service Clinic Unit (KLIPPER) innovation which gains considerable advantages, both internal and external stakeholder. KLIPPER is a licensing consultation program for investors who will make complex building construction permits. Furthermore, KLIPPER improves both license output and law-abiding performances. This study explores process behind innovation. It is prominent objective because scholars have argued innovation process as a blackbox and a conundrum. We applies innovation process theory which separates to the threefold linear stages of the procesess (initiation, implementation and diffusion). This study used qualitative approach to interpret involved actor’s experiences in innovation process. Finally, the study sums up that innovation is an evident work, it is not an accidental action because it can be traced back through to the dramatic steps, consequently it could be proposed as a framework to carry out innovative program for the others local governments agencies